The Impact of Losing in a Competition on the Willingness to seek Further Challenges - Thomas Buser (Tinbergen Institute, 2014)
How do people react to setbacks and successes? I introduce a new measure of challenge-seeking to determine the effect of winning and losing in a competition on the willingness to seek further challenges. Participants in a lab experiment compete in two-person tournaments and are then informed of their score and the outcome of the competition. Conditional on the score, winning or losing is random. Participants then have to decide on a performance target for a second round: the higher the target, the higher the potential reward, but participants who do not reach the target earn nothing. I find that, conditional on first round scores, losers go for a more challenging target but perform worse, leading to lower earnings and a higher probability of failure. These findings could have important implications for our understanding of individual career paths. Early outcomes coul d alter the probability of success and failure in the long term.
Keywords: C91; D03; J16; J01; 330; competition; challenge seeking; career decisions; laboratory experiment; gender